Papel do tecido adiposo de indivíduos obesos sobre células tumorais de mama - Andrade, Isadora Ramos de (2018)
Obesity is a multifactorial disease characterized by a meta-inflammation sustained by the adipose tissue (TA). It constitutes a major public health problem because of its impact on public coffers and especially because of its association with several diseases, including cancer. Evidences show that obesity is linked to a worse prognosis and an increased risk of death in women with breast cancer. In order to evaluate the influence of adipose tissue (AT) on tumor cells, we stimulated, in vitro, human mammary adenocarcinoma cells (MCF-7 and MDA-MB-231) with conditioned medium (CM) or extracellular vesicle fraction (MPs) secreted by AT derived from obese or lean individuals, which were obtained during bariatric or plastic surgery, respectively. Our objective was to investigate the effects of secretion from obese AT on breast cancer cells, as well as the mechanisms and signaling pathways behind them. MCF-7 and MDA-MB-231 cells were stimulated for 24 h with 20% (V/V) MC or MPs (20 μg/ml) derived from obese or lean individuals; the cell proliferation assay was evaluated by the MTT method in the presence or absence of the MAPK/ERK pathway inhibitor (PD98059); cell migration was performed by the wound healing method and cell invasion by transwell migration (coated with 1% gelatin), both in the presence or absence of the PI3K/AKT pathway inhibitor (LY294002); ERK and AKT expression (in MCF-7 and MDA-MB-231 cells) and expression of MMP-2 and 9 (in MPs) were evaluated by Western blotting; for the Matrigel tubulogenesis assays, endothelial cells (HMEC-1) were incubated with the culture supernatant from untreated MDA-MB-231 cells or MDA-MB-231 cells previously treated with the CM derived from the obese AT; MMP-9 mRNA expression was evaluated by real-time PCR; the proteolytic activity of MMP-2 and 9 present in the MPs was evaluated by zymography. Our results demonstrated that MC and MPs from obese AT increased the proliferation of MCF-7 cells, without altering it in MDA-MB-231 cells. On the other hand, MC and MPs from obese AT increased the migration and invasiveness of MDA-MB-231 cells. In addition, we observed that both the CM and MPs released by obese AT increased ERK phosphorylation in MCF-7 cells, while only MPs increased the phosphorylation of AKT in MDA-MB-231 cells. The MAPK/ERK inhibitor decreased the proliferation of MCF-7 cells, whereas the PI3K/AKT inhibitor decreased both migration and invasion of MDA-MB-231 cells. Additionally, we observed that the treatment of the HMEC-1 cells with the supernatant from MDA-MB-231 cells previously treated with the CM from the obese AT showed increased tubulogenic capacity. It is important to note that this effect was not observed when HMEC-1 cells were treated with only the CM from obese AT. Interestingly, the MPs released by obese AT were enriched in bioactives MMP-2 and 9, possibly explaining the increase in the invasive capacity of these cells. Taken together, our results indicate that the microenvironment of obese AT influences priority functions for the progression of breast cancer, increasing the malignancy of the tumor cells through the secretion by molecules and MPs from AT with pro-tumor activities.